Solubility parameters based on refractive index data of ionic liquid - Abdullah, S.B. (Trans Tech Publications Ltd, 2014)
This article reports on the estimation of solubility parameters using refractive index for a series of imidazolium-based ionic liquids (ILs) and their dependencies on the carbon number of alkyl sidechain of cation and anion. Gathering about 35 ILs of refractive indices data from the literature, the solubility parameters estimation fit well with the suggested correlation. The precision of the estimated solubility parameters obtained indicates that the refractive index-solubility parameters correlation can be an alternative tool to estimate solubility parameter value for ILs. Â© (2014) Trans Tech Publications, Switzerland.